2017
DOI: 10.5296/jad.v3i1.10650
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Long-Term Return after the Great East Japan Earthquake: Lessons from Hirono Town

Abstract: The Great East Japan Earthquake and the ensuing tsunami and nuclear accident at Fukushima Daiichi displaced more than 340,000 people. Four years later, more than 70,000 people were still living in temporary housing. This article summarizes findings from a series of structured interviews with people from Hirono Town that were still living in temporary housing four and a half years after the triple catastrophe. The interviews sought to understand why people were still in temporary housing, rather than moving bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…More recently, Bruch et al (2017) investigated barriers to the long‐term return of evacuees from the town of Hirono in the aftermath of the Tõhoku earthquake and tsunami and the Fukushima Daiichi nuclear accident on 11 March 2011. The authors found that older people and those who stayed in temporary housing for longer periods were more likely to return.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Bruch et al (2017) investigated barriers to the long‐term return of evacuees from the town of Hirono in the aftermath of the Tõhoku earthquake and tsunami and the Fukushima Daiichi nuclear accident on 11 March 2011. The authors found that older people and those who stayed in temporary housing for longer periods were more likely to return.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that older people and those who stayed in temporary housing for longer periods were more likely to return. Younger people said that they prioritised places with better educational opportunities for their children, job prospects, and social amenities (Bruch et al, 2017). In addition, based on a survey of 520 households from areas that were affected by the Fukushima Daiichi disaster, Munro and Managi (2017) found that people with children were less likely to return, whereas higher income households were more likely to do so.…”
Section: Introductionmentioning
confidence: 99%
“…Bruch et al (2017), however, found, to our surprise, that more than 70% of the residents in the temporary housing felt very happy or somewhat happy about their stay. They had both positive reasons for staying and negative reasons for not leaving temporary housing.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the following initiatives are required for improvement: survival and continuation of the affected communities, inputs from the communities to the decision-makers by way of the local governments, and long-term policies that take account of the changing livelihood and opinion of the evacuees. Bruch et al (2017) addressed the issue of how the evacuees living in temporary housing regard their livelihood and their return home. They conducted a series of structured interviews with people from Hirono Town, who were still living in temporary housing four and a half years after the disaster, to understand why people were still in temporary housing, rather than moving back to Hirono Town or on to more permanent arrangements in other locations.…”
Section: Findings Out Of Case Studiesmentioning
confidence: 99%
“…Although it took 15 days, the government eventually recommended, but did not order and did not coordinate, the evacuation of local communities, leaving the affected people to evacuate on their own. The government subsequently declared an exclusion zone of 20 kilometers (Bruch et al, 2017;Rangieri & Ishiwatari, 2014). The final count of people left completely homeless by the destruction was about 556,000 that by October 2011 had been reduced to 65,753.…”
Section: The Japanese Earthquake-tsunami-nuclear Catastrophe and Massmentioning
confidence: 99%